URBAN INFRASTRUCTURE FLOODING IN SOUTHERN ONTARIO: A CASE STUDY APPROACH TO DETERMINE CAUSALITY (PART TWO) - Kulkarni, Tanuja (Assurances)

(untitled) (HEC Montréal, 2000)
Three case study cities were chosen from a number of urban flood events that were identified through local newspapers. Peterborough, Sarnia and Ottawa all experienced urban floods in the same year and are all located southern Ontario. Cursory review of the three events indicates that there may be different causal factors that influenced the urban floods. They were chosen to be case study cities because they fall in one region of Canada, are in the same climate zone and the flood events, though similar, appeared to be the result of different features of the urban setting. Precipitation data for each case study city was gathered, and the regional climate data was reviewed. Intensity, duration and frequency tables were considered for these cities but only maximum rainfall for 15 minutes, one hour and 24 hours were compared. Land use change maps in the areas surrounding the flood events were developed over a minimum of 20 years for each city. Approximately 1km2 was measured around the flooded area and compared over time. The change from permeable to impermeable land cover was considered as a mechanism for increased flooding. The sewage systems were also examined to determine if they could be a cause for urban flooding in these cities.